Penerapan Face Shield Bagi Tenaga Medis Untuk Menangani Pasien Covid-19 di Kota Batu Jawa Timur - Mochamad Arif Irfai1; Muchlis Arif; Nova Kristiana; I Made Arsana4 (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2021)
The purpose of this activity is to assist the government in providing and distributing face shields for medical personnel at referral hospitals to treat covid-19 patients. At first we analyzed the problems with partners (hospitals and community health centers). The results of the analysis show that hospitals and health centers lack a helmet-face shield for medical personnel to treat covid-19 patients. Based on the results of discussions and requests from the partner. Then the design is carried out to manufacture a helmet-face shield. There are 2 PPE made, The first type is only a face shield and the second type is obtained a helmet design that is equipped with a face shield or can be called a helmet-face shield. At the end of the activity, questionnaires were distributed to respondents consisting of doctors, nurses and other medical personnel. Respondents were selected randomly in health facilities in Batu, East Java. The response from medical personnel has generally been positive. This can be seen from the questionnaires distributed to respondents. More than 90% of the results of the questionnaire stated that helmet-face shield and face shield products could be accepted by health workers.